The polycomb group protein EZH2 inhibits lung cancer cell growth by repressing the transcription factor Nrf2. Issue 17 (10th June 2014) - Li, Ziming; Xu, Ling; Tang, Naiwang; Xu, Yunhua; Ye, Xiangyun; Shen, Shengping; Niu, Xiaomin; Lu, Shun; Chen, Zhiwei
Abstract : EZH2 is a key component of the polycomb PRC2 complex and functions as a histone H3 Lys27 (H3K27) trimethyltransferase. Here we show that EZH2 is down‐regulated in human non‐small cell lung cancer and low EZH2 expression predicts poor survival. Further we demonstrate that EZH2 inhibits lung cancer cell proliferation and colony formation in vitro and growth in vivo. We found that EZH2 binds to the promoter of Nrf2, where it increases H3K27me3 and represses Nrf2 expression. Finally, Nrf2 seems to be essential for the hyper proliferation of lung cancer cells in the absence of EZH2. Abstract : EZH2 is down‐regulated in human NSCLC and low EZH2 predicts poor survival. EZH2 regulates lung cancer cell growth in vitro and in vivo. EZH2 inhibits the expression of Nrf2 by targeting H3K27me3. Nrf2 is essential for the function of EZH2.